PENGAWASAN ANTE NATAL CARE MENCEGAH ANEMIA IBU HAMIL DI PUSKESMAS KOTA KABUPATEN ENDE - khrispina owa; Rif’atunisa; Maria Salestina Sekunda (Kelimutu Nursing Journal, 2026)
Maternal mortality is always associated with pregnancy and childbirth, whereas pregnancy and childbirth are physiological conditions in a woman's life stage. When a woman is pregnant, physiologically in the plasma hematology system there will be a very large increase of 50%-60%, but it is not balanced by an increase in blood cells of only 25-30%. This has an impact on decreasing blood hemoglobin levels (anemia), so that O2 carried to the fetus is low and has fatal consequences for the mother and fetus. Ende Regency, the area that contributes the most cases of anemia in pregnant women is the City Health Center with the number of pregnant women experiencing anemia amounting to 338 people or 65.5%. Therefore, supervision of pregnant women is needed to prevent anemia. Research Objective: To prove the implementation of antenatal care supervision to prevent anemia in pregnant women. Methodology: Qualitative descriptive research with a phenomenological approach. Results: Pregnant women's knowledge about anemia is good, but has not been followed by behavior to prevent anemia. Supervision of pregnant women in health facilities is good, but they have not complied with the advice of midwives and nutritionists regarding eating nutritious food, meaning they are not used to eating green vegetables that contain raw materials for making erythrocytes in the bone marrow to increase hemoglobin. Discussion: There is a need for regular health education and promotion related to the nutrition of pregnant women during ANC supervision as an effort to prevent anemia in pregnant women